Tari Melayu Malaysia : satu kajian berdasarkan festival tari kebangsaan - Mohd. Nefi Imran ([Kuala Lumpur : Penerbit Akademi Seni Budaya dan Warisan Kebangsaan, 2011)
Malaysian dance and folk dancing.
Revision of the author's thesis (Ph. D.)--Universiti Malaya, 2004.
Includes bibliographical references (p. 262-271).
In Malay.
Keywords: Dance -- Malaysia; Folk dancing -- Malaysia